SERVICE OPERATIONS MANAGEMENT(SOM) - Ríos Ramos, Franklin (2006)
This paper is a literature review about theoretical approaches that have emerged in the service field. The first purpose is to determine the state of the question in the research of Service Operations Management. The second is to offer a guide for future researches.